Comparison of crestal bone loss around submerged and Non- submerged replace implants - Panjnosh M.; Siadat H.; AliKhasi M.; AliHoseini M. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: It is well recognized that implant treatment is common worldwide, but the approach to success is not predictable because of bone loss that occurs around the implants. Also there are many factors affecting crestal bone loss around the implants that one of them is the surgical protocol of implant installation. The purpose of this investigation was to evaluate the amount of crestal bone loss around the Replace implants installed according to submerged and non- submerged treatment protocol. "nMaterials and Methods: In this study, 11 patients received 34 implants. In each patient (unilateral or bilateral mandible), one of the implants was placed with submerged procedure and in the other one non- submerged procedure was used. In a period of 3 months a temporary partial denture that covered the implants was used. After 3 months the submerged fixture was exposed, impression was performed and fixed prosthesis was fabricated. Loss of crestal bone at each implant was measured. These measurements have been done at surgical times, over a period of 3 months after implant installation and 6 months after the delivery of the fixed prosthesis. The measurement was done with digital subtraction radiography. Data was analyzed by Wilcoxon Signed Ranks test. "nResults: Three months after implant placement, submerged groups showed statistically more crestal bone loss (0.65±0.71) than non-submerged (0.41±0.53) group (p=0.02). After 6 months the mean value of crestal bone loss in submerged group was 0.21±0.40 mm and in non submerged group was 0.29±0.49 mm. This data indicated no statistically significant difference between the two groups of implants (p>0.05). "n "nConclusion: Our results are in accordance with previously published studies and confirm that the value of crestal bone loss in submerged and non-submerged groups after 3 and 6 months were similar and in acceptable limit.